189k views
4 votes
Solve the equation to this problem

Solve the equation to this problem-example-1

2 Answers

4 votes

Answer:

x = - 6/7

Explanation:

To start, 1x is just 1 times x, which you can just write as x.

x+3 = 8x+9

Then, you can bring x over to the other side of the equation, meaning it becomes -x. You can also think about subtracting x from both sides so it cancels out on the left.

3 = 8x+9-x

Next, do the same for the 9, so your equation looks like this:

3-9 = 8x-x

Just simplify it:

-6 = 7x

Finally, divide -6 by 7 to find x.

So, x = -6/7

User Neoraptor
by
5.3k points
0 votes
X=-6/7 or x=-0.857 ✌️
User RCH
by
5.2k points